(untitled) - Loverro, Thom (Hoboken, N.J., 2006)
Who is the greatest quarterback in Redskins history? Baugh? Jurgensen? Theismann? Rypien? However you answer that question, you'll find plenty of evidence to support your argument in Hail Victory. This comprehensive history of the tradition-rich Washington Redskins puts you on the 50-yard line to witness all of the team's most memorable moments, meet its greatest players, and hear what they have to say about the brightest and darkest moments from the team's past. In this compelling account of seventy years of Redskins history
Keywords: Washington Redskins (Football team),Washington Redskins (Đội bóng); History,Lịch sử